ANALISIS PEMELIHARAAN SARANA DAN PRASARANA SEKOLAH DI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 3 PADANG - Asnita Asnita; Armiati Armiati; Efni Cerya (Universitas Negeri Padang, 2018)
This study purposing to determine the process of maintenance of school facilities and infrastructure in Sekolah Menengah Kejuruan (SMK) Negeri 3 Padang.This research is categorized as qualitative descriptive with data sources coming from interviews, direct observation to the object of research and documentation. The validity of the data was tested using Source Triangulation. The results showed that overall maintenance activities had not been carried out optimally. This is caused by: 1) difficulty in disbursing funds used for maintenance activities, 2) inadequate library space, 3) lack of bookshelves in the library room, 4) the school does not use control cards as proof of liability answer. Maintenance activities are carried out by means of periodic, continuous and preventive maintenance. Meanwhile, the solutive action taken is to repair itself if there are damaged facilities or infrastructures, striving to create and increase the number of bookshelves in the library room. By carrying out optimal maintenance activities, it can extend the economic value and maximize the utilization of the facilities and infrastructure in the school. Keywords: Analysis, Maintenance, Facilities and Infrastructure.